The Penguin Book of Contemporary Irish Poetry - Fallon, Peter, 1951-; Mahon, Derek, 1941-2020. (London : Penguin, 1990)
An anthology of the work of 30 contemporary Irish poets beginning with poets of the 1950s generation. The selection includes poetry from the north of Ireland in the 1960s and 1970s.
Includes index.
Keywords: English poetry -- Irish authors; Irish poetry -- Translations into English; English poetry -- 20th century; Northern Ireland -- Poetry; Ireland -- Poetry